2000
DOI: 10.1101/gad.831500
|View full text |Cite
|
Sign up to set email alerts
|

The Forkhead transcription factor UNC-130 is required for the graded spatial expression of the UNC-129 TGF-β guidance factor in C. elegans

Abstract: Secreted proteins required for cellular movements along the circumference of the body wall inA fundamental question in development is how cellular movements are guided. Studying mutations that specifically affect guidance has proven to be an effective way to investigate this process. In the free-living nematode Caenorhabditis elegans, the secreted UNC-6/netrin guidance cue is expressed ventrally while UNC-5 and UNC-40/DCC (deleted in colorectal cancer), predicted receptors for UNC-6, are expressed in axons and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 40 publications
2
70
0
Order By: Relevance
“…We crossed tm3335 and tm3607 with a C. elegans line, named evls82b, in which DB and DA neurons were labeled with the unc-129:: GFP reporter (Figure 3a). 21 In young-adult (4 days old) btbd-10(tm3335);evls82 and btbd-10(tm3607);evls82 worms, 10.9 % (n=129) Reduced expression of BTBD10 is neurotoxic M Nawa et al 14 DA and DB motor neurons were randomly lost and 6.7% and 7.8% of worms lost at least one DB and DA motor neurons, respectively, whereas no evls82 worms lost DB and DA neurons (Figure 3b). We also noted that 4.8% of btbd-10(tm3335);evls82 and 2.9% of btbd-10(tm3607);evls82 young-adult worms had at least one mislocalized DB or DA motor neurons, whereas no evls82 worms contained a mislocalized neuron (Figure 3c).…”
Section: Resultsmentioning
confidence: 99%
“…We crossed tm3335 and tm3607 with a C. elegans line, named evls82b, in which DB and DA neurons were labeled with the unc-129:: GFP reporter (Figure 3a). 21 In young-adult (4 days old) btbd-10(tm3335);evls82 and btbd-10(tm3607);evls82 worms, 10.9 % (n=129) Reduced expression of BTBD10 is neurotoxic M Nawa et al 14 DA and DB motor neurons were randomly lost and 6.7% and 7.8% of worms lost at least one DB and DA motor neurons, respectively, whereas no evls82 worms lost DB and DA neurons (Figure 3b). We also noted that 4.8% of btbd-10(tm3335);evls82 and 2.9% of btbd-10(tm3607);evls82 young-adult worms had at least one mislocalized DB or DA motor neurons, whereas no evls82 worms contained a mislocalized neuron (Figure 3c).…”
Section: Resultsmentioning
confidence: 99%
“…We found that unc-130(ev505) causes a mild ray axon defect similar to that seen in unc-6 and unc-40 mutants ( Figure 3D, Table 4). For dorsally orientated migrations of gonadal distal tip cells and for dorsoventral guidance of growth cones in formation of the motor neuron commissures, unc-130 acts in a pathway parallel to the UNC-6/netrin guidance pathway (Nash et al 2000). It encodes a forkhead transcription factor that acts by repressing unc-129 expression in ventral body muscles (Nash et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…For dorsally orientated migrations of gonadal distal tip cells and for dorsoventral guidance of growth cones in formation of the motor neuron commissures, unc-130 acts in a pathway parallel to the UNC-6/netrin guidance pathway (Nash et al 2000). It encodes a forkhead transcription factor that acts by repressing unc-129 expression in ventral body muscles (Nash et al 2000). We examined the effect of mutation in unc-129, which encodes a C. elegans TGF-b involved in motor axon guidance .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mutation in unc-119, which encodes a protein acting as a regulator of axon branching (Maduro and Pilgrim, 1995;Knobel et al, 2001), caused axon length defects in both the NSM (shorter axons) and M2 (longer axons) neurons, but caused excessive branching only in the M2 neurons. A mutation in the unc-129/TGFbeta pathway, which guides circumferential axons in C. elegans Nash et al, 2000;Ikegami et al, 2004), causes truncations or loss of the NSM major processes, but has little effect on the M2 neurons. Similarly, a mutation in the semaphorin-2 gene, smp-2 Ikegami et al, 2004), cause absence or truncation of the NSM major processes, but has no effects on the M2 neurons or the NSM thin process.…”
Section: Growth Cones Guidance Pathways and Robustnessmentioning
confidence: 99%